1817 Discovered Dead During Sleep in Causal Pathway of Mortality Among Children with Cerebral Palsy: Case Series and Systematic Review. (October 2012) - Holmes, L; Karatas, A; Kirk, D; Connor, J; Rogers, K; Miller, F
Abstract : Background and Aims: To report thirteen cases of children with cerebral palsies (CP) discovered dead during sleep (DDDS) and to synthesize the research literature on CP survival. Method: We utilized case series to describe the common features among patients DDDS between 1993 and 2011. Using our medical records, we extracted data on demographics, treatment, and co-morbidities. In addition using the appropriate search terms, we searched the Medline and other electronic data bases for articles published between 1966 and 2011. Further, we synthesized the literature and provided evidence on clinical conditions that could be associated with CP mortality in relation to DDDS, obstructive sleep apnea syndrome (OSAS) and sleep related breathing disorders (SRBD) management. Results: Between 1993 and 2011 there were 177 reported deaths, of which 13 occurred as a result of being DDDS at home. All the deceased patients had Gastrointestinal feeding tube, seizure, respiratory disorders, and were non-ambulatory. A greater proportion had scoliosis and hip dislocation surgeries. DDDS in our sample may be associated with these conditions; and OSAS/SRBD as evidenced in literature. Conclusion: Pulmonary problems and disorders were the most common co-morbidity, due probably to oxygen desaturation (< 70%), prolonged sleep apnea such OSAS and SRBD. Since there were no data on Polysomnography (PSG) and autopsy, it was difficult to account for specific sleep disorders that might have contributed to DDDS. We recommend a routine PSG and treatment of OSAS and SRBD, given their high prevalence among CP patients, especially those with disturbed nocturnal sleep and noisy breathing.